Racial/Ethnic differences in clinical and biochemical type 2 diabetes mellitus risk factors in children. (5th July 2013) - Rosenbaum, Michael; Fennoy, Ilene; Accacha, Siham; Altshuler, Lisa; Carey, Dennis E.; Holleran, Stephen; Rapaport, Robert; Shelov, Steven P.; Speiser, Phyllis W.; Ten, S.; Bhangoo, Amrit; Boucher‐Berry, Claudia; et al.
<x xml:space="preserve">Abstract</x> Objective To examine whether periadolescent children demonstrate the significant racial/ethnic differences in body fatness relative to BMI and in the prevalence and relationship of body composition to risk factors for type 2 diabetes (T2DM) as in adults. Design and Methods Family history of obesity and T2DM, anthropometry, insulin sensitivity and secretory capacity, lipids, and cytokines (IL‐6, CRP, TNF‐α, and adiponectin) were examined in a cohort of 994 middle school students (47% male, 53%, female; 12% African American, 14% East Asian, 13% South Asian, 9% Caucasian, 44% Hispanic, and 8% other). Results Fractional body fat content was significantly greater at any BMI among South Asians. There were racial/ethnic specific differences in lipid profiles, insulin secretory capacity, insulin sensitivity, and inflammatory markers corrected for body fatness that are similar to those seen in adults. Family history of T2DM was associated with lower insulin secretory capacity while family history of obesity was more associated with insulin resistance. Conclusions Children show some of the same racial/ethnic differences in risk factors for adiposity‐related comorbidities as adults. BMI and waist circumference cutoffs to identify children at‐risk for adiposity‐related comorbidities should be adjusted by racial/ethnic group as well as other variables such as birthweight and family history.